2014
DOI: 10.1007/s10029-014-1292-y
|View full text |Cite
|
Sign up to set email alerts
|

An international consensus algorithm for management of chronic postoperative inguinal pain

Abstract: There is a need for guidelines with regard to management of CPIP. This algorithm can serve as a guide with regard to the diagnosis, management, and treatment of these patients and improve clinical outcomes. If an expectative phase of a few months has passed without any amelioration of CPIP, a multidisciplinary approach is indicated and a pain management team should be consulted. Pharmacologic, behavioral, and interventional modalities including nerve blocks are essential. If conservative measures fail and surg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
89
0
4

Year Published

2016
2016
2019
2019

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 115 publications
(95 citation statements)
references
References 24 publications
2
89
0
4
Order By: Relevance
“…Surgical interventions are usually considered as a last option once pain is recalcitrant. (Lange 2015). The number of neurectomies depends on the preference of the attending surgeon.…”
Section: Description Of the Conditionmentioning
confidence: 99%
“…Surgical interventions are usually considered as a last option once pain is recalcitrant. (Lange 2015). The number of neurectomies depends on the preference of the attending surgeon.…”
Section: Description Of the Conditionmentioning
confidence: 99%
“…Nerve blocks interfere with neural transmission and can temporarily reduce neuralgia, serving therapeutic and diagnostic capabilities. [1] Nonetheless, there is paucity in the literature on success rates of nerve blocks as a treatment option for neuropathic inguinodynia. [3,10] Further, their temporary effect and requirement for multiple administrations represents a drawback of their use as a therapeutic modality.…”
Section: Discussionmentioning
confidence: 99%
“…[16] However, foreign body removal alone does not always lead to favorable results as it might fail to address irreversible nerve damage that may have been established, which can continue to be a source of neuropathic pain. [1] Heise et al demonstrated that mesh removal plus neurectomy led to pain relief in 62% of chronic inguinodynia patients. [14] Ultimately, the results in our patient after combined mesh replacement and ilioingual neurectomy, were excellent.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations